On modelling multi-agent systems based on large language models - Shchetinin, Eugeny Yu; Velieva, Tatyana R.; Yurgina, Lyubov A.; Demidova, Anastasia V. (Discrete and continuous models and applied computational science, 2025)
The article studies the effectiveness of implementation of multi-agent systems based on large language models in various spheres of human activity, analyses their advantages, problems and challenges. The results of the research have shown that multi-agent systems based on large language models have significant potential and wide opportunities in modelling various environments and solving various tasks.